2013
DOI: 10.2166/wst.2013.014
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic irradiation as pretreatment for the reduction of excess sludge by Fenton-acclimation treatment

Abstract: Ultrasonic irradiation as a pretreatment of Fenton-acclimation treatment was investigated to enhance the efficiency of sludge reduction and effectiveness of operating cost. A series of batch experiments were conducted to optimize the reaction conditions for ultrasonic-Fenton treatment. Separate ultrasonic treatment suggested that input power of 0.4 W/mL and ultrasonic time of 10 min were the optimal conditions for sludge disintegration, and the efficiency was reduced with the increase of sludge mixed liquor su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Some studies have been reported on the degradation of bisphenol A in waste water sludge by ultrasonication, Fenton’s oxidation or combination of both (ferro-sonication) pre-treatment processes1819. Ultrasound coupled with Fenton oxidation pre-treatment of sludge was also investigated to enhance the efficiency of sludge reduction and effectiveness of operating cost20. Herein, we use ultrasound coupled with Fenton oxidation pre-treatment of sludge to promote sludge disintegration.…”
mentioning
confidence: 99%
“…Some studies have been reported on the degradation of bisphenol A in waste water sludge by ultrasonication, Fenton’s oxidation or combination of both (ferro-sonication) pre-treatment processes1819. Ultrasound coupled with Fenton oxidation pre-treatment of sludge was also investigated to enhance the efficiency of sludge reduction and effectiveness of operating cost20. Herein, we use ultrasound coupled with Fenton oxidation pre-treatment of sludge to promote sludge disintegration.…”
mentioning
confidence: 99%
“…Ozone decomposition proceeds with the following five-step chain reaction, as is shown in Eqs. (9)(10)(11)(12)(13) [40]. These equations show that alkaline conditions can increase ozone decomposition to form free radicals such as hydroxyl radicals ( • OH), superoxide O •À 2 À Á , and ozonide ions O •À 3 À Á .…”
Section: Effect Of Ph Of the Sludgementioning
confidence: 99%
“…The conventional methods for sludge treatment and disposal (e.g., landfill and incineration) [11] are confronting severe challenges due to more stringent environmental regulations. Various novel reduction technologies to treat excess sludge have been developed, such as thermal, ultrasonic, mechanical, alkaline, or oxidative treatments [12][13][14][15], along with biological treatment processes.…”
Section: Introductionmentioning
confidence: 99%
“…Equations 7 and 8 detail the scavenging effect of H2O2 on OH radicals (Feng et al 2003;Qiu et al 2013 . HO2 + .…”
Section: Total Cod Reduction and Suspended Solids Reductionmentioning
confidence: 99%